Global epidemiology of nonalcoholic fatty liver disease—Meta‐analytic assessment of prevalence, incidence, and outcomes. Issue 1 (22nd February 2016) - Younossi, Zobair M.; Koenig, Aaron B.; Abdelatif, Dinan; Fazel, Yousef; Henry, Linda; Wymer, Mark
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a major cause of liver disease worldwide. We estimated the global prevalence, incidence, progression, and outcomes of NAFLD and nonalcoholic steatohepatitis (NASH). PubMed/MEDLINE were searched from 1989 to 2015 for terms involving epidemiology and progression of NAFLD. Exclusions included selected groups (studies that exclusively enrolled morbidly obese or diabetics or pediatric) and no data on alcohol consumption or other liver diseases. Incidence of hepatocellular carcinoma (HCC), cirrhosis, overall mortality, and liver‐related mortality were determined. NASH required histological diagnosis. All studies were reviewed by three independent investigators. Analysis was stratified by region, diagnostic technique, biopsy indication, and study population. We used random‐effects models to provide point estimates (95% confidence interval [CI]) of prevalence, incidence, mortality and incidence rate ratios, and metaregression with subgroup analysis to account for heterogeneity. Of 729 studies, 86 were included with a sample size of 8, 515, 431 from 22 countries. Global prevalence of NAFLD is 25.24% (95% CI: 22.10‐28.65) with highest prevalence in the Middle East and South America and lowest in Africa. Metabolic comorbidities associated with NAFLD included obesity (51.34%; 95% CI: 41.38‐61.20), type 2 diabetes (22.51%; 95% CI: 17.92‐27.89), hyperlipidemia (69.16%; 95% CI: 49.91‐83.46%), hypertension (39.34%; 95% CI: 33.15‐45.88), and metabolic syndrome (42.54%; 95% CI: 30.06‐56.05). Fibrosis progression proportion, and mean annual rate of progression in NASH were 40.76% (95% CI: 34.69‐47.13) and 0.09 (95% CI: 0.06‐0.12). HCC incidence among NAFLD patients was 0.44 per 1, 000 person‐years (range, 0.29‐0.66). Liver‐specific mortality and overall mortality among NAFLD and NASH were 0.77 per 1, 000 (range, 0.33‐1.77) and 11.77 per 1, 000 person‐years (range, 7.10‐19.53) and 15.44 per 1, 000 (range, 11.72‐20.34) and 25.56 per 1, 000 person‐years (range, 6.29‐103.80). Incidence risk ratios for liver‐specific and overall mortality for NAFLD were 1.94 (range, 1.28‐2.92) and 1.05 (range, 0.70‐1.56). Conclusions : As the global epidemic of obesity fuels metabolic conditions, the clinical and economic burden of NAFLD will become enormous. (Hepatology 2016;64:73–84)